(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article analyzes the psychological stress factors and pressure observed in sapper operations. It is scientifically substantiated that the application of modern robotic technologies and remotely controlled devices in explosive ordnance disposal (EOD) practice can significantly reduce the psychological burden on military personnel. In addition, the article examines mechanisms for minimizing life-threatening risks through robotic systems, optimizing decisionmaking processes, and reducing mental fatigue. The research findings confirm the necessity of widely introducing technological solutions as a psychological protection factor in sapper training